Hiding in plain sight: unmasking computer science heroes in K-6 classrooms - Elledge, Kiera Shuler (Kansas State University, 2024)
This research project employs a case study design to examine how K-6 non-computer science (CS) trained teachers can be effectively prepared to teach CS, metaphorically unmasking hidden superheroes in the education system. Grounded in the Technological Pedagogical Content Knowledge (TPACK) framework, the study also integrates Bandura’s Theory of Self-Efficacy, the Crawl-Walk-Run-Fly Model (CWRF), and Bruner's Spiral Curriculum. Through detailed case studies, the research investigates teachers' professional development experiences, their evolving self-efficacy, and their practical application of CS concepts in the classroom. Data collected from surveys, interviews, and the researcher’s journal are analyzed to identify best practices and challenges. This program is designed not only to inform strategies for teacher training programs that will enhance the integration of CS education in diverse educational settings, but also to foster a mindset of growth, bravery, and resilience. Through a series of workshops, hands-on activities, and ongoing support, teachers will acquire the skills they need and, more importantly, the courage to venture into uncharted territory. The findings reveal that with the right tools and support systems in place, K-6 teachers can indeed become proficient in teaching computer science. More significantly, they develop a newfound confidence that permeates their teaching practice, inspiring them to continue to be life-long learners who boldly guide their students to embrace the challenges of the digital age.
Keywords: Elementary computer science; Teacher professional development; Technology, pedagogy and content knowledge (TPACK) framework; Self-efficacy; Crawl-walk-run-fly (CWRF) model